Lipopolysaccharide-induced expression of Th1/Th2 cytokines in whole neonatal cord and adult blood: role of nuclear factor-kappa B and p38 MAPK - Koch, Lutz; Fritzsching, Benedikt; Frommhold, David; Pöschl, Johannes (Neonatology, 2011)
Background: Sepsis continues to be a leading cause of morbidity and mortality in newborns. - Objective: As both nuclear factor-kappa B (NF-ĸB) and p38 mitogen-activated protein kinase (MAPK) appear to be critical mediators in inflammatory response, we studied the effects of lipopolysaccharide (LPS) on expression and function of NF-ĸB and p38 MAPK in whole neonatal cord and adult blood. - Methods: Th1/Th2 cytokine concentrations and phosphorylation of NF-ĸB and p38 MAPK were determined by flow-cytometric analysis. - Results: Tumor necrosis factor-alpha (TNF-α), IL-6, and IL-10 concentrations were significantly elevated in supernatants of neonatal and adult blood after LPS stimulation for 4 h. IFN-γ, IL-4, and IL-2 showed no significant alterations. Furthermore, TNF-α concentrations were significantly higher in adult compared to neonatal blood after LPS stimulation. Stimulation with LPS resulted in significantly decreased activation of p38 MAPK in neonatal blood, whereas NF-ĸB showed no difference. Following inhibition of p38 MAPK with the specific inhibitor SB-202190, levels of TNF-α and IL-6 significantly decreased in neonatal and adult blood, whereas pharmacological inhibition of NF-ĸB with SC-514 showed no significant effect on cytokine expression. - Conclusions: We conclude that p38 MAPK phosphorylation is crucially involved in LPS activation and could explain the differences in early cytokine response between neonatal and adult blood.